1989
DOI: 10.1016/0014-5793(89)81221-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of intact hepatocytes with either the phorbol ester TPA or glucagon elicits the phosphorylation and functional inactivation of the inhibitory guanine nucleotide regulatory protein Gi

Abstract: The antiserum AS7 can specifically immunopreeipitate a-Gi from membrane extracts as well as from a mixture of purified ct-Gi and a-Go as ascertained using [azP]ADP-ribosylated G-proteins. Using this antiserum to immunopreeipitate ~t-G~ from hepatocytes labelled with a2p it was evident that ~t-Gi was phosphorylated under basal (resting) conditions. Challenge of hepatocytes with the tumour promoting phorbol ester TPA, however, elicited a marked enhancement of the phosphorylation state of ~t-Gi. This was accompan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 29 publications
1
31
1
Order By: Relevance
“…It is in. tercstinB to note that it has been shown that TPA blocks 0i function in liver cells [201 and that this effect is associated with the phosphorylation of Gi or [20]; however, the blockade of Gi function observed in liver cells is differer~t to that observed in platele(s, i,e. the inhibitory action of Ilydrolysis-resistant analogues of GTP is blocked [20], Aeknowledllemenl,t; The authors thank Ms Guadalu p= gamirex for typinll the manuscript, This researcll was partially supported by a grant rrom DGAPA (1N021889),…”
Section: Febs Letter";mentioning
confidence: 96%
“…It is in. tercstinB to note that it has been shown that TPA blocks 0i function in liver cells [201 and that this effect is associated with the phosphorylation of Gi or [20]; however, the blockade of Gi function observed in liver cells is differer~t to that observed in platele(s, i,e. the inhibitory action of Ilydrolysis-resistant analogues of GTP is blocked [20], Aeknowledllemenl,t; The authors thank Ms Guadalu p= gamirex for typinll the manuscript, This researcll was partially supported by a grant rrom DGAPA (1N021889),…”
Section: Febs Letter";mentioning
confidence: 96%
“…Phosphorylation of G proteins by, for example, protein kinases C1C. W.Taylor C (Sagi-Eisenberg, 1989: Pyne et al, 1989 or receptor tyrosine kinases (Zick et al, 1986;Valentine-Braun et al, 1986;O'Brien et al, 1987) (Jakobs et al, 1985).…”
Section: G Proteins Remembermentioning
confidence: 99%
“…Pertussis toxin-catalysed ADP-ribosylation was performed according to Pyne et al (1989). Membranes (10Ltg) were combined with a final concentration (mM): thymidine 30, potasium phosphate 80 (pH 7.5), arginine 20, MgCl2 1 and to this was added 2,Ci [32P]-NAD' 0.02, and these were then combined with preactivated pertussis toxin (0.64 pLg/assay) and incubated at 37°C for 30 min.…”
Section: Introductionmentioning
confidence: 99%
“…This is a typical result from the experiment performed at contrast, methacholine pretreatment of tracheal smooth least 10 times on different membrane preparations. (Katada et al, 1985;Zick et al, 1986;O'Brien et al, 1987;Pyne et al, 1989;1992a) and adenylyl cyclase (Yoshimasa et al, 1987). The molecular events that govern the functional antagonism between the muscarinic receptor and the adrenoceptor Llysed are unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation